2022
DOI: 10.4028/p-er55r2
|View full text |Cite
|
Sign up to set email alerts
|

Water Holding and Release Properties of Bacterial Cellulose Produced from Oil Palm Frond Juice

Abstract: Water holding and release properties are important characteristics for a dressing material in wound healing. In the present study, the water holding capacity (WHC) and water release rate (WRR) of BC films produced from oil palm frond (OPF) juice were investigated. The juice was inoculated with Acetobacter xylinum in 24-well plates and incubated at 30 °C for 7 days under static conditions. The films were further dried by three different methods; air-, oven-and freeze-drying. The dried BC was characterized for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Skin cells such as keratinocytes and fibroblasts have also demonstrated good biocompatibility with the BC composite loaded with nanoparticles (Sabarees et al, 2022). Moreover, our recent study has shown that AgNPs impregnated into BC composite can provide a favourable moisture environment with good water holding and release properties comparable to pure BC (Abu et al, 2021;2022).…”
Section: P R E S Smentioning
confidence: 99%
“…Skin cells such as keratinocytes and fibroblasts have also demonstrated good biocompatibility with the BC composite loaded with nanoparticles (Sabarees et al, 2022). Moreover, our recent study has shown that AgNPs impregnated into BC composite can provide a favourable moisture environment with good water holding and release properties comparable to pure BC (Abu et al, 2021;2022).…”
Section: P R E S Smentioning
confidence: 99%